2016
DOI: 10.1186/s12906-016-1237-3
|View full text |Cite
|
Sign up to set email alerts
|

Chemical analysis of Punica granatum fruit peel and its in vitro and in vivo biological properties

Abstract: BackgroundThe medical application of pomegranate fruits and its peel is attracted human beings. The aim of the present study was to evaluate the in vitro α-Glucosidase inhibition, antimicrobial, antioxidant property and in vivo anti-hyperglycemic activity of Punica granatum (pomegranate) fruit peel extract using Caenorhabditis elegans.MethodsVarious invitro antioxidant activity of fruit peel extracts was determined by standard protocol. Antibacterial and antifungal activities were determined using disc diffusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(39 citation statements)
references
References 28 publications
4
27
0
1
Order By: Relevance
“…Thus, indicating superior capability of this plant in other in vitro assays as well. The high reducing ability of P. granatum is analogous with the previous antioxidant studies on its fruit peel [25, 26]. In addition to antioxidant ability, the eco-friendly biological waste and nutraceutic resource i.e.…”
Section: Discussionsupporting
confidence: 73%
“…Thus, indicating superior capability of this plant in other in vitro assays as well. The high reducing ability of P. granatum is analogous with the previous antioxidant studies on its fruit peel [25, 26]. In addition to antioxidant ability, the eco-friendly biological waste and nutraceutic resource i.e.…”
Section: Discussionsupporting
confidence: 73%
“…Interestingly, different fractions of aqueous or alcohol extracts of pomegranate peel have different spectra of antibacterial activity, as measured in disk diffusion assays, and different authors present conflicting data on the inhibitory effects of aqueous extract fractions (65)(66)(67)(68)(69)(70). We note, however, that antibacterial effects have been observed, even when using dried rather than fresh peel, and that pomegranate peel extracts have also been reported to exhibit antiviral (71) and antifungal (66,67,70) effects. We were unable to find any relevant data on the in vivo effects of these four ingredients with regard to treating soft tissue wounds or infections, except for one small study which compared the healing of excisional wounds in mice treated topically with either gentamicin ointment or pomegranate extract: in this study, all mice treated with pomegranate extract showed complete wound healing (72).…”
Section: Results and Discussion Network Analysis Of Remedies For Skinmentioning
confidence: 77%
“…The bactericidal effects of bile are long established: bile salts disrupt bacterial membranes, and this quality contributes to host-mediated control of bacterial overgrowth in the gut (63,64). Interestingly, different fractions of aqueous or alcohol extracts of pomegranate peel have different spectra of antibacterial activity, as measured in disk diffusion assays, and different authors present conflicting data on the inhibitory effects of aqueous extract fractions (65)(66)(67)(68)(69)(70). We note, however, that antibacterial effects have been observed, even when using dried rather than fresh peel, and that pomegranate peel extracts have also been reported to exhibit antiviral (71) and antifungal (66,67,70) effects.…”
Section: Results and Discussion Network Analysis Of Remedies For Skinmentioning
confidence: 99%
“…Extraction of metabolites of the fruit samples is carried out according to Ref. with some modifications. Dried powder of fruit sample was soaked in methanol in the ratio of 1:10 (0.5 g of sample in 5 mL of 100% methanol) for 30 min at room temperature at 150 rpm.…”
Section: Methodsmentioning
confidence: 99%